Compressive Behaviour of RC Column with Fibre Reinforced Concrete Confined by CFRP Strips - A. M. Vasumathi; K. Rajkumar; G. Ganesh Prabhu (Advances in Materials Science and Engineering)
The structural application of synthetic fibre reinforced concrete (FRC) has become widespread in the construction industry in order to satisfy the requirement of the earthquake resistant structures. Research conducted so far are focused on the structural behaviour of RC column externally confined with FRP composites, while studies are needed to address the behaviour of FRP strengthened RC column fabricated using fibre reinforced concrete. With the intention that the experimental investigation was carried out to evaluate the feasibility use of CFRP composite strips in strengthening of RC column made with fibre reinforced concrete. Circular synthetic Polypropylene fibre was used in the rate of 0.50% in the volume of concrete. CFRP strips having a width of 50 mm were used to confine the column and the experimental parameters were effective spacing between the CFRP strips (20 mm and 30 mm) and the number of CFRP layers (one, two and three). The externally bonded CFRP strips counteract the lateral expansion of the concrete significantly by providing restraining effect and thus effect enhanced the stiffness of the column. The column strengthened with CFRP strips showed a maximum of 198.87% and 91.75% enhancement in axial deformation control and ultimate strength, respectively, compared to that of reference column. From the test results obtained, it is suggested that CFRP strips with the spacing of 20 mm and 30 mm can be used in strengthening of RC column made with FRC; however the column confined with 30 mm spacing provides an economical advantage compared to that of 20 mm spacing.